Polarographic Study of Mixed Ligand Complexes of Cd(II) in Khetri Ore Sample with Cadaverine and Dicarboxylic Acid in Aqueous Medium - Sharma, Jaswant; Mukerjee, S.K. (Asian Journal of Chemistry, 2010)
In present work the polarographic study. of mixed ligand complexes of Cd(II) in Khetri one sample with cadaverine and various dicarboxylic acids such as adipic acid, malonic acid, maleic acid, succinic acid or phthalic acid are reported.